Mixed vitamin C and zinc diet supplements co-administered with artemether drug improved haematological profile and survival of mice infected with Plasmodium berghei - Felicia N. Ekeh; Nkiru E. Ekechukwu; Chimdinma F. Chukwuma; Ifeanyi Oscar N. Aguzie; Chinenye M. Ohanu; Chike Ebido; Stanley N. Oluah (Food Science and Human Wellness)
Iron and zinc deficiencies is common in malaria endemic areas and contributes to morbidity. Vitamin C and zinc combined supplements have been hypothesized as a remedy. This study evaluated the effect of different combinations of vitamin C and zinc on haematological parameters and mortality of Plasmodium berghei-infected mice (Mus musculus). A three-week trial was carried out to assess haematological changes and mortality of mice after 3-day artemether treatment co-administered with vitamin C - zinc supplements. Grouping was based on combinations of vitamin C and zinc. Weight, packed cell volume (PCV), white blood cell count (WBC), red blood cell count (RBC), haemoglobin concentration (HB), and mortality were assayed weekly. The supplement improved PCV, HB, mean cell volume (MCV) and mean cell haemoglobin (MCH). Mice mortality was higher in the absence of the supplement, though the difference was not significant (χ2 = 5.214, P = 0.5167). Parasitaemia was not reduced by the supplement. A 30:70 vitamin C - zinc supplement performed better than other combinations used. Therefore, vitamin C - zinc supplement play roles in the management of malaria, since they improved PCV and HB, and lowered mortality rate, complementing the therapeutic effect of artemether. Keywords: Dietary supplement, Food supplement, Micronutrient, Zinc, Vitamin C, Malaria, Nutritional medicine